1999
DOI: 10.1111/j.1553-2712.1999.tb01210.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Intra‐abdominal Injuries in Children Hospitalized Following Blunt Torso Trauma

Abstract: Abstract. Objective: To determine the utility of the ED physical examination and laboratory analysis in screening hospitalized pediatric blunt trauma patients for intra-abdominal injuries (IAIs). Methods: The authors reviewed the records of all patients aged <15 years who sustained blunt traumatic injury and were admitted to a Level 1 trauma center over a fouryear period. Patients were considered high-risk for IAI if they had any of the following at ED presentation: decreased level of consciousness (GCS < 15),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 31 publications
0
22
2
Order By: Relevance
“…Some of these studies did not describe the abdominal examination findings, did not mention the mental status of the patient, or did not define an "abnormal" abdominal examination. 13,14 This shortcoming was addressed in a recent study by Holmes et al, 15 who described an increased likelihood of IAI among children presenting with abdominal abrasions or abnormal chest examination findings. These findings supported those of Allen et al, 16 who demonstrated an increased incidence of hollow viscus injury (13.5%) in pediatric blunt trauma patients presenting with abdominal wall ecchymosis.…”
Section: Fig 2 Relative Importance Of Variables In Modeling By Recumentioning
confidence: 95%
See 1 more Smart Citation
“…Some of these studies did not describe the abdominal examination findings, did not mention the mental status of the patient, or did not define an "abnormal" abdominal examination. 13,14 This shortcoming was addressed in a recent study by Holmes et al, 15 who described an increased likelihood of IAI among children presenting with abdominal abrasions or abnormal chest examination findings. These findings supported those of Allen et al, 16 who demonstrated an increased incidence of hollow viscus injury (13.5%) in pediatric blunt trauma patients presenting with abdominal wall ecchymosis.…”
Section: Fig 2 Relative Importance Of Variables In Modeling By Recumentioning
confidence: 95%
“…Although studies have demonstrated a poor correlation between elevated AST or ALT and severity of liver injury, these tests have been found to predict the presence or absence of solid organ or other abdominal injury. 6,7,17,18 Holmes et al 15 found that an AST exceeding 200 or an ALT exceeding 125 alone identifies IAI in almost two thirds of pediatric trauma patients. In the current study population, 69% of the patients with IAI had an AST exceeding 131 or an ALT exceeding 105.…”
Section: Fig 2 Relative Importance Of Variables In Modeling By Recumentioning
confidence: 98%
“…24,25 Results from several previous studies indicated that hematuria might also be an accurate predictor of renal injury. 15,[26][27][28] Unfortunately, the three children identified with hematuria did not have radiologic testing to evaluate for possible renal or bladder injury. Optimal practice should include further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…This was a particular problem for the 3 children with hematuria who did not have abdominal imaging, as several studies have shown that hematuria is a good marker for intra-abdominal trauma among children with non-inflicted injury. 15,[26][27][28] We have therefore presented conservative estimates of the percentage of positive screens, assuming that none of the unscreened children had OAT, and noting the minimum percentage of children with OAT. Even with these conservative estimates, the proportion of physically abused children with OAT is high enough to warrant screening, at least for children under 3 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is still unknown as to who should undergo an abdominal CT in hemodynamically stable patients without the above findings. Elevations of serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) have been suggested to be indicative of liver injury [1][2][3][4][5]11]. Therefore, we conducted this study to determine the usefulness of AST and ALT as screening tests in predicting liver injuries in pediatric torso trauma patients.…”
Section: Introductionmentioning
confidence: 99%